(untitled) (Socio-Economic Development Panorama, 2008)
This article highlights upon how Hindu high caste Nepalese women, hereafter connoting Nepalese women construct gender knowledge and internalize subordinated gender identities through the complex socialization process. It also focuses on relevant religious and cultural sources of knowledge that support to construct gender identities as male or female specific culture, and its manifestation, as is its reflection on everyday life. Gender has gained unprecedented momentum in Nepal, as women representing the second best half of the societies are fighting tooth and nail against multivariate forms of discriminations. Only building mutual empathy and harmonizination of gender identity in an amicable manner by building trust will it eventually help to break the tip of the iceberg against women’s subordination. In the same way, this article focuses on the multipolar ways adopted to deconstruct gender identities and re-ordered gender relationships between men and women. The exploration aims towards the contribution of Hindu religious texts that constructs a wider gender knowledge of high caste Hindu women. It focuses on the reflection of subordinated gender identities connected in the ideology through practices incurred in a Hindu woman’s everyday life. In the same way, the article also illustrates on how the overall deconstruction process of gender knowledge overtakes over the society. It explores on the role of subordinated gender identities of women in the changing context. The findings of the article support the views of post-structural feminism that advocates deconstructing the myth that men always tend to stand as oppressor and the women are always the oppressed and the victim of gender discrimination. Instead of this, discourse and discussion, advocacy and awareness programs are offered to transfer subordinated situation of women to re-order gender relations between men and women through reciprocation of empathy and trust building measures. Key words: discriminations, gender identity, subordinated gender identities, gendered habitus, deconstructionists, gender culture, religious philosophical texts, enculturation, patriarchal family Socio Economic Development Panorama Vol. 1, No. 3(2008) pp. 7-20